The spectrum of intermediate SCN8A‐related epilepsy. (10th April 2019) - Johannesen, Katrine M.; Gardella, Elena; Encinas, Alejandra C.; Lehesjoki, Anna‐Elina; Linnankivi, Tarja; Petersen, Michael B.; Lund, Ida Charlotte Bay; Blichfeldt, Susanne; Miranda, Maria J.; Pal, Deb K.; Lascelles, Karine; Procopis, Peter; et al.
Summary: Objective: Pathogenic variants in SCN8A have been associated with a wide spectrum of epilepsy phenotypes, ranging from benign familial infantile seizures (BFIS) to epileptic encephalopathies with variable severity. Furthermore, a few patients with intellectual disability (ID) or movement disorders without epilepsy have been reported. The vast majority of the published SCN8A patients suffer from severe developmental and epileptic encephalopathy (DEE). In this study, we aimed to provide further insight on the spectrum of milder SCN8A ‐related epilepsies. Methods: A cohort of 1095 patients were screened using a next generation sequencing panel. Further patients were ascertained from a network of epilepsy genetics clinics. Patients with severe DEE and BFIS were excluded from the study. Results: We found 36 probands who presented with an SCN8A ‐related epilepsy and normal intellect (33%) or mild (61%) to moderate ID (6%). All patients presented with epilepsy between age 1.5 months and 7 years (mean = 13.6 months), and 58% of these became seizure‐free, two‐thirds on monotherapy. Neurological disturbances included ataxia (28%) and hypotonia (19%) as the most prominent features. Interictal electroencephalogram was normal in 41%. Several recurrent variants were observed, including Ile763Val, Val891Met, Gly1475Arg, Gly1483Lys, Phe1588Leu, Arg1617Gln, Ala1650Val/Thr, Arg1872Gln, and Asn1877Ser. Significance: With this study, we explore the electroclinical features of an intermediate SCN8A ‐related epilepsy with mild cognitive impairment, which is for the majority a treatable epilepsy.